Fra massemedier til mediesystem - om kodediskussionen i systemteoretisk medieforskning [From mass media to media system - code discussions in systems theoretical media research] - Eskjær, Mikkel Fugl (MedieKultur: Journal of media and communication research, 2010)
Systems theoretical media research raises the question whether the mass media constitute a unified institution, or whether the media, due to their internal differences, should be considered individually and independent of each other. By inscribing the media in a general social theory, systems theory conceptualises the media as an autonomous functional system. This intention is most clearly illustrated by the efforts to identify a shared code for the entire media system. Based on the media theory of Niklas Luhmann, this paper offers a critical presentation of the code discussion within systems theoretical media research. The first part of the paper briefly introduces the systems theoretical notion of a code as well as Luhmann’s definition of the media system as organised and regulated by the code of information. The second part presents a number of alternative suggestions and definitions of the media system’s code, which both indicate the scope of systems theoretical media research, but also point to some of the limitations in the systems theoretical approach. In the last part, the paper takes a critical look at the systems theoretical code discussion by arguing that a too narrow focus on code definitions is blocking a more productive investigation of the conditions, evolution, and autonomy of the media system.